ASSESSMENT OF NEAR-REDUCTION UNION RATES WITH CONSERVATIVE HUMERUS FRACTURE TREATMENT - A JAMA, ABDIRASHID (Biological and Clinical Sciences Research Journal, 2024)
This study attempts to determine near-reduction union rates with non-operative treatment of humeral shaft fractures, assess alignment and functional outcomes, and compare these with historic and surgical management approaches. Methods: This was a cross-sectional study at the Department of Orthopedics, Jinnah Postgraduate Medical Centre, Karachi, from January 2024 to June 2024. Twenty patients aged between 17–72 years who suffered from humeral shaft fractures were inducted through consecutive sampling. The conservative treatment mode was applied with a "U"-shaped coaptation splint, where alignment was assessed on radiographs, and functional outcome was achieved with a grading system. Data was analyzed using SPSS-20 regarding union rates, functional recovery, and factors influencing treatment success. Results: In this study of 20 fractures, the initial angulation was 30%, while deviations in sagittal plane alignment in the anterior or posterior direction were seen in 45%. Nineteen of these fractures united within an average time of 42 days in men and 44 days in women; one case showed a delayed union of 13 weeks. Functional results were also excellent, with 60% of patients achieving Grade V function, signifying the absence of pain or limitations, and 35% reporting Grade IV, meaning minimal limitations. Comparisons with historical studies showed that conservative management was similarly successful, with a high union rate and acceptable functional outcome in most cases noted. Conclusion: The conservative approach to treating humeral shaft fractures, characterized by limited immobilization with early mobilization, had a high union rate with excellent functional outcomes equal to surgical interventions. Success with treatment was considerably influenced by patient age, type of fracture, and degree of initial displacement, thus indicating that treatment has to be individualized. This study supports a conservative approach as a modality of choice in managing humeral shaft fractures, emphasizing individuated care for optimum recovery and satisfaction of patients.